Kouluorganisaatioiden turvallisuuskulttuuri omatoimisen varautumisen arvioinnin perusteella : Monitapaustutkimus perusopetuksen kouluissa - Lindfors, Eila; Somerkoski, Brita; Korkeaniemi, Arttu (Hallinnon tutkimuksen seura, 2026)
The safety culture of a school organization based on evaluation of self-preparedness – a multi-case study in comprehensive education schools
School safety is a legal right for every learner and staff. This study asks: what is the level of safety culture of comprehensive education schools from the perspective of self-preparedness and prevention measures? This multi-case study examines ten comprehensive education schools using document analysis. The data consists of ten self-preparedness evaluation reports that evaluate the safety of schools on a scale of weak – progressive and based on group discussions. The data is analysed from the perspective of safety management, risk management, safety-related documents, structural fire safety, security and safety communication and competence. The safety culture was mostly reactive in some schools and proactive measures were lacking. We conclude that comprehensive education schools need greater expertise and practical support in developing their safety culture.